Mechanism of Astragalus Polysaccharide in Alleviating Bovine Mammary Fibrosis Through ROS/NLRP3 Inhibition and EMT Regulation - Jiang Zhang; Kejiang Liu; Tingji Yang; Hongwei Duan; Longfei Xiao; Quanwei Zhang; Yong Zhang; Weitao Dong; Xingxu Zhao (Antioxidants)
Mastitis in dairy cows, typically caused by bacterial infection, is a common inflammatory condition of the mammary tissue that leads to fibrosis, adversely affecting cow health, milk production, and dairy product quality. Astragalus polysaccharide (APS) has shown effectiveness in alleviating inflammation and fibrosis in various organs. The study employed lipopolysaccharide (LPS) to induce fibrotic conditions in two experimental systems: MAC-T bovine mammary epithelial cells and Kunming mouse models. Key parameters, including relative gene mRNA expression, protein levels, and reactive oxygen species (ROS) levels, were assessed using RT-qPCR, Western blotting (WB), and 2’,7’-Dichlorofluorescin diacetate (DCFH-DA) techniques, while histological analysis of mammary tissue was performed using H&E and Masson trichrome staining. Measuring malondialdehyde (MDA) levels, assessing the enzyme activities of catalase (CAT), and superoxide dismutase (SOD) were two methods of assessing oxidative stress. These methods were also tested in mouse mammary glands. APS significantly decreased ROS concentrations (p < 0.01), restored oxidative stress balance in mice (p < 0.05), and reduced fibrosis and inflammation, as demonstrated by histological observations and analysis. It also exerted regulatory effects on fibrosis markers (E-cadherin, N-cadherin, α-SMA) and inflammation markers (NLRP3, ASC, Caspase-1, IL-1β), as demonstrated by changes in their mRNA and protein expression. These findings endorse APS’s viability as an alternative therapeutic agent for mammary fibrosis therapy by demonstrating its ability to inhibit epithelial-mesenchymal transition (EMT) in vitro and mammary fibrosis in vivo, while also mitigating ROS production and reducing inflammation.